2019
DOI: 10.2217/fmb-2019-0122
|View full text |Cite
|
Sign up to set email alerts
|

Update on Drug-Repurposing: Is it Useful for Tackling Antimicrobial Resistance?

Abstract: There are several advantages to drug repurposing including leveraging pre-existing safety and clinical data to skip extensive Phase I safety studies and enter clinical trials at Phase IIa, which not only positively impacts development times and costs but also negates risks "

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 20 publications
(20 reference statements)
0
36
0
Order By: Relevance
“…Mazumdar et al [ 35 ] demonstrated the role of DCF in the inhibition of DNA synthesis, in addition to a moderate membrane-damaging action against Listeria monocytogenes ATCC 51744. Similarly, several authors proposed the inhibition of DNA synthesis through binding to the DNA polymerase III β subunit as a mode of action of NSAIDs, preventing DNA replication and repair or impairment of membrane activity [ 26 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mazumdar et al [ 35 ] demonstrated the role of DCF in the inhibition of DNA synthesis, in addition to a moderate membrane-damaging action against Listeria monocytogenes ATCC 51744. Similarly, several authors proposed the inhibition of DNA synthesis through binding to the DNA polymerase III β subunit as a mode of action of NSAIDs, preventing DNA replication and repair or impairment of membrane activity [ 26 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, preclinical, pharmacokinetic, pharmacodynamic and toxicity profiles and the side effects of these drugs are well known, which facilitates other therapeutic applications [ 19 , 25 ]. This pre-existing data allow skipping extensive phase I safety studies and starting clinical trials at phase IIa, reducing substantially the development time and cost [ 26 ]. In recent years, some studies acknowledged the antimicrobial effects of several classes of non-antibiotic drugs, more precisely, the nonsteroidal anti-inflammatory drugs (NSAIDs) [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to combat the increasing emergence of this fungal pathogen, it is imperative that new treatments be found. As opposed to a lengthy and expensive de novo pathway for drug discovery, repurposing or repositioning of existing drugs may represent a cost effective and faster approach to finding compounds with antifungal properties that can be readily used in patients [34][35][36][37]. To this end, here we screened The Pathogen Box ® library from Medicines for Malaria Venture (MMV; https://www.mmv.org/mmv-open/pathogen-box), a diverse library of approximately 400 drug-like compounds assembled by MMV, in search for inhibitors of C. auris.…”
Section: Introductionmentioning
confidence: 99%
“…This situation highlights the need to understand the mechanisms of drug resistance and tolerance, and the search for novel antifungal agents (62,63). As a few antifungal compounds are coming to market because their development is time-consuming and expensive, repositioning or repurposing drugs which are already licensed is an interesting and faster opportunity for the identification of novel antifungals agents (64)(65)(66). By using the repurposing strategy, many compounds have already been identified as new potential drugs against several diseases including parasitosis, protozooses and mycoses (64,(66)(67)(68)(69)(70)(71).…”
Section: Introductionmentioning
confidence: 99%